Green infrastructure site prioritization to improve urban flood resilience in Monterrey and Brussels using a decision support model - Mina Khodadad; Mohsen Sanei; Ismael Aguilar-Barajas; Leopoldo Eduardo Cárdenas-Barrón; Aldo Iván Ramírez-Orozco; Agatino Rizzo; Ahmed Z. Khan (Scientific Reports)
Abstract Green infrastructure (GI) has been increasingly associated with urban flood resilience as it provides benefits in protecting communities from flood dangers and improving socio-economic capabilities. In order to optimize the GI advantages, it is necessary to engage in strategic prioritizing of implementation areas, considering local conditions. Despite a growing interest in connecting GI and flood resilience, there is still a lack of strategic-oriented GI planning models aimed at enhancing urban flood resilience. This study has introduced the Flood Resilience-based Urban Green Infrastructure Site Priority (FRUGISP) model, which employs a GIS-based multi-criteria assessment to determine the urban regions that should be prioritized for the implementation of GI systems, based on their flood resilience levels. The model was used to map the priority areas in Monterrey, Mexico, and Brussels, Belgium. Despite their distinct features, both cities face flood challenges. The results showed regions of utmost importance based on the flood resilience index and land availability for GI implementation. The model has the potential to be applied to other urban areas grappling with flood issues, providing guidance to decision-makers in selecting high-priority locations for GI projects. This approach can effectively address the difficulties posed by urban floods, ensuring the resilience of urban areas.